Turismo sostenible en Urabá (2017)
The present article is carried out as a graduation project by students of tourism business administration, of the Faculty of business science of the University of San Buenaventura, where a State of the art was previously held for the research project "Model of sustainable tourism management for Urabá by integrating the value chain and the lifeblood, as a contribution to the peace process that is taking place in the region" by the universities: Universidad Pontificia Bolivariana, Universidad de San Buenaventura, and the Universidad Santo Tomas, which aims at creating a model of sustainable tourism management for Urabá; Considering the state of the art mentioned above, is this article focuses on sustainable tourism, in order to establish whether the sub region of Urabá is a sustainable destination; The research is based on literary analysis and interviews, which is given to sustainable tourism as an agent that minimizes environmental damage and maximizing the economic benefits.